(untitled) (Bangladesh Medical Journal Khulna, 2016)
Early pregnancy loss is a frustrating experience for both the patient and the physician. Approximately 5% of couples trying to conceive have 2 consecutive miscarriages and approximately 1% couples have 3 or more consecutive losses. Objective of this study is to determine whether therapy with dydrogesterone or Human chorionic Gonadotrophin hormone (HCG) in history of repeated pregnancy loss during the first trimester of pregnancy will improve pregnancy outcome. This is a prospective open comparative study.Women having early pregnancy presenting to a private clinic with history of early pregnancy loss, having no medical disorder were included in this study. Eligible subjects were randomised to receive either dydrogesterone 20mg daily or injection Human Chorionic Gonadotrophins (HCG) 5000 iu intramuscularly at 72 hours interval up to fourteen weeks of pregnancy or no additional treatment. Follow up of those patients were done with transabdominal ultrasonography. Hundred women were recruited. There was no statistically significant difference between the three groups with regard to pretreatment status. The continuing pregnancy success rate was higher in women treated with dydrogesterone (79.17%) and highest with Injection Human Chorionic, Gonadotrophin (86.36%) compared with women received no treatment (70%), (p=0.358). Hormonal support with either dydrogesterone or Human Chorionic Gonadotrophin may increase the chances of a successful pregnancy in women with a history of spontaneous abortion. Bang Med J (Khulna) 2015; 48 : 7-10